Iron Magnetic Nanoparticles Coated with Different Loadings of Polyvinylpyrrolidone: Evaluation of Magnetic Properties and Morphology - Shikh Mohd Shahrul Nizan Shikh Zahari; Nurul Hafizah Muhamad Tajuddin; Nur Fatin Izzati Che Sam; Kholoud M.H. Elzaneen; Poppy Puspitasari; Cameron C. Weber; Nurazilah Mohd Zainon (Elsevier, 2024)
Indexed by WOS/Scopus/ERA